Efficacy and Safety of Electroacupuncture in the Treatment of Cerebral Infarction: Systematic Review and Meta-Analysis - Lan Xiang Wang; Wei Hong Li; Fang He (Applied Bionics and Biomechanics)
Purpose. The goal of this study was to see if electroacupuncture was effective and safe in the management of cerebral infarction. PubMed, Embase, Cochrane Library, and Web of Science were used to conduct a comprehensive literature survey. Methods. Basic features of 7 studies were identified using the searching strategy. The investigation was found in PubMed, Embase, and Web of Science, with the most recent search being in March 2022. “Electroacupuncture,” “cerebral infarction,” and their permutations were among the MeSH terms and free words used. As literature, two reviewers independently used a standardized form to gather pertinent data from qualifying research. Results. 157 literatures were identified and evaluated. Electroacupuncture improved the BI score in individuals with cerebral infarction (mean difference=0.10, 95 percent CI: 0.00-0.20, p=0.04). Electroacupuncture enhanced BI score in individuals with cerebral infarction (mean difference=0.10, 95 percent CI: 0.00-0.20, p=0.04). The effects of electroacupuncture increased Fugl-Meyer index in patients with cerebral infarction (mean difference=25.92, 95% CI: 25.28-26.56, p<0.00001). Electroacupuncture effects decreased CSS in patients with cerebral infarction in the experiment group (mean difference=−2.10, 95% CI: -2.53–-1.67, p<0.0001). Electroacupuncture also reduced CSS individuals with cerebral infarction in the control group; however, there was no statistically significant (risk difference=0.06, 95 percent CI: 0.02-0.13, p=0.12). Conclusion. This study demonstrated that electroacupuncture helped decreased CSS in patients with cerebral infarction.